Don Quixote - Cervantes Saavedra, Miguel de, 1547-1616. ([New York] : Penguin Books, 2003)
The story of the adventurous knight-errant and his squire Sancho Panzo, who set out to right the wrongs of the world.
Introduction -- Further reading -- Translating Don Quixote -- Acknowledgments -- Chronology -- Note of the text.
Keywords: Quixote, -- Don (Fictitious character) -- Fiction; Knights and knighthood -- Spain -- Fiction; Spain -- Social life and customs -- Fiction